2019
DOI: 10.1016/j.jvs.2019.06.120
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abdominal Aortic Aneurysms in the United States: Re-evaluating the Screening Guidelines

Abstract: A single-center analysis of pediatric patients with acute IFAT from 2011 to 2019 was conducted. Medical records and vascular laboratory studies were reviewed retrospectively. Patients with one or more surveillance US studies were included. Thrombus resolution was defined as multiphasic flow throughout the index limb without evidence of echogenic intraluminal material by US. Time to resolution of thrombus was assessed using Kaplan-Meier analysis. Results: Fifty-four limbs in 50 patients were identified. The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies regarding the epidemiology of AAA in Western countries vary in the definition of AAA and/or the study population. The prevalence of AAA in these studies ranged from 1.3% to 8% [ 11 , 12 , 13 , 14 , 15 , 16 ], and the annual incidence of newly diagnosed AAA in screened populations ranged from 0.4% to 0.67% [ 17 , 18 ]. Although most Asian countries have not yet adopted a screening program for AAA, making it difficult to determine its exact prevalence, the incidence of AAA is generally thought to be lower in Asian than in Western populations [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding the epidemiology of AAA in Western countries vary in the definition of AAA and/or the study population. The prevalence of AAA in these studies ranged from 1.3% to 8% [ 11 , 12 , 13 , 14 , 15 , 16 ], and the annual incidence of newly diagnosed AAA in screened populations ranged from 0.4% to 0.67% [ 17 , 18 ]. Although most Asian countries have not yet adopted a screening program for AAA, making it difficult to determine its exact prevalence, the incidence of AAA is generally thought to be lower in Asian than in Western populations [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence reported in these studies is comparable to, if not higher than what has been reported in some Western countries. [ 46 47 ]…”
Section: Discussionmentioning
confidence: 99%